URGENSI KESEIMBANGAN ILMU PENGETAHUAN & PENDIDIKAN BUDI PEKERTI DALAM PEMBENTUKAN KARAKTER ANAK DI DUSUN KRAJAN DESA WANGKAL KECAMATAN GADING KABUPATEN PROBOLINGGO - Atikatur Rifkia; Zahida I’tisoma Billah (Najah: Journal of Research and Community Service, 2025)
This service aims to: (1) Find out how far the balance of knowledge and character education for children in Wangkal village is (2) Cooperate with formal and non-formal educational institutions in the local village (3) Invite parents to pay more attention to behavior children's morals when outside school (4) Providing advice or input to figures and parents as first teachers to take appropriate steps in order to improve the balance of knowledge gained and morals as a practice in life. This research took place in the Krajan hamlet, Wangkal Village, Gading District, Probolinggo Regency, using the face-to-face method. Starting from the preparation stage, to the implementation stage. And the result is that the difficulty level of the balance between knowledge and practice is a lack of full attention from parents, because character education in schools is not enough to provide learning about ethics and ethics in just a few hours a day. It is parents who should be the first teachers in shaping the personality, mindset, attitude patterns and lifestyle of children. But what happens a lot is that parents hand over their children's moral/moral education to the school at random.